QUALITY MANAGEMENT OF PRODUCTIVE AGE-BASED PERSONAL DEVELOPMENT IN THE SYSTEM OF LIFELONG EDUCATION - A. Yuriev; N. Kozyrev; O. Kozyreva (Вестник Северо-Кавказского федерального университета, 2022)
The article highlights and theorizes the foundations of quality management of productive age-appropriate development of a person in the system of lifelong education. The concept and models of quality management ofproductive age-appropriate development of a personality in the system of lifelong education have been clarified. The functions, principles, priorities, values and tendencies of management and quality assurance of the productive age-appropriate development of the personality in the system of lifelong education have been determined. The possibilities of using ideas and approaches of classical and innovative pedagogy in theorization and clariication of the quality of productive age-appropriate development of a personality in the system of lifelong education are revealed and scientifically substantiated. The possibilities of modeling the technology of productive age-appropriate development of a personality in the system of continuous education, taking into account the orientation of the professional training of the individual and the level ofprofessional education (SPE, VO, DPO), have been determined. The pedagogical conditions for optimizing the possibilities of managing the quality of the productive age-appropriate development of the individual in the system of lifelong education are identiied.